A consolidação da formação do professor-pesquisador da Pós-Graduação em Educação da UFPA: o(s) produto(s) científico(s) em foco - BAHIA, Cinara Ciberia Meireles (Universidade Federal do Pará, 2012)
This study theme running through the field of higher education had the task to speak about the object the consolidation of teacher-researcher at the Graduate Education of UFPA, which reflected an epistemological concern in understanding the educational actions developed in the post- graduate and currently is developing the relationship between labor-productivity research that finds its roots still in the genesis of the Graduate Program in Brazil in the 60s. The overall objective was to analyze the teaching of the teacher-researcher at Graduate Education, Federal University of Pará - UFPA, from the consolidation of its post-graduate training, and focused on five specific chapters of the dissertation, namely: to identify the legal and epistemological giving voice to teaching in Higher Education as a link with the concept of teacher-researcher checking of institutional arrangements that govern the teaching work at the Graduate; analyze the consolidation process of the formation of teacher-researchers of Graduate Education, UFPA; examine the level of scientific productivity of teachers and researchers of Graduate Education and UFPA; see how the teaching work of these researchers has been evaluated by the External Evaluation Commission of CAPES. Dedicating to the following problematic: As the work of the teacher-researcher is created after the consolidation of its post-graduate training? The issues which triggered the problems discussed in each chapter: How does the teacher work developed in higher education has been characterized within the epistemological approach that involves the concept of teacher-researcher? To what extent the institutional aspects shape the teaching activities developed in the Graduate, particularly at the Institute of Education Sciences UFPA? This reveals the introduction of the PhD thesis of teacher-researchers? As the scientific productivity of these teacher-researchers has been developing within the Lattes? As the CAPES evaluated the teaching in the Graduate Education of the UFPA time gap from 2003 to 2010? Given the issues, the study was built on a theoretical and methodological approach grounded in historical and educational, this time authors as Carvalho (2003) and Lombardi (2004) made up the dialogue necessary to explain what triggered the option in the choice of the five sources examined in the historical study, literature on the epistemology of the teacher-researcher, requirements officers, issues of doctoral theses of the current faculty PPGED UFPA, lattes curricula of these subjects and finally the evaluation sheets from CAPES apply PPGED to the years 2004 and 2007 concerning the triennial evaluation coordinated by the Authority. Was an instrumental case study concerned with understanding the educational activity in the post-graduate, considered the delay of 2003-2010. Among the results, it was found mainly to the consolidation of the teacher-researcher is in the stage of completion of the consolidation of PhD postgraduate training, just the starting point, since it is built on experience in the teaching, in the post-graduate degree in their contact with the various investigative processes that surround this field of meanings and contradictions that the teacher actually consolidates its investigative activity.